Prepositions and ESL learners: the Malaysian scenario - Roslim, Norwati; Mukundan, Jayakaran (Australian International Academic Centre, 2014)
This article presents a review of the literature on prepositions with a focus on definitions and main difficulties faced by Malaysian students. It further highlights recommendations about the role of syllabus designers, textbook writers and teachers in meeting these challenges. It is hoped that this article could provide a platform for any further studies on prepositions.